2021
DOI: 10.1093/nar/gkab421
|View full text |Cite
|
Sign up to set email alerts
|

CPA: a web-based platform for consensus pathway analysis and interactive visualization

Abstract: In molecular biology and genetics, there is a large gap between the ease of data collection and our ability to extract knowledge from these data. Contributing to this gap is the fact that living organisms are complex systems whose emerging phenotypes are the results of multiple complex interactions taking place on various pathways. This demands powerful yet user-friendly pathway analysis tools to translate the now abundant high-throughput data into a better understanding of the underlying biological phenomena.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 55 publications
0
24
0
Order By: Relevance
“…When single cell expression information was assessed by Gene Ontology (GO) Consensus Pathway Analysis (CPA) [ 31 ] the DE genes were found to be related to developmental pathways, mechanotransduction, and genomic stress/repair mechanisms. Figure 2 presents the GO-CPA mapping and expression heatmaps for the highest DE genes from each pathway.…”
Section: Resultsmentioning
confidence: 99%
“…When single cell expression information was assessed by Gene Ontology (GO) Consensus Pathway Analysis (CPA) [ 31 ] the DE genes were found to be related to developmental pathways, mechanotransduction, and genomic stress/repair mechanisms. Figure 2 presents the GO-CPA mapping and expression heatmaps for the highest DE genes from each pathway.…”
Section: Resultsmentioning
confidence: 99%
“…KEGG pathway analysis of DEGs showed that enriched pathways included glutathione metabolism and the pentose phosphate pathway, similar to the results obtained from GSE57065 ( Figure 1D ). Consensus pathway analysis (CPA) ( https://bioinformatics.cse.unr.edu/.software/cpa/ ) 26 was used to analyze the ferroptosis-related genes between healthy and septic patients and found that there were 40 kinds of genes that changed after sepsis ( Figure 1E ). Acyl-CoA synthetase long-chain family member 4 (ACSL4), a key indicator and regulator of ferroptosis, which could activate long-chain polyunsaturated fatty acids to participate in the synthesis of membrane phospholipids, was increased significantly in the septic patients with an AUC of 0.854 (95% CI = 0.638–1.000) ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%
“…While the techniques to do so can differ, generally a consensus is taken across several methods to determine the final set of pathways that are interesting in some statistically significant way. Examples to do so include the R packages EGSEA [ 58 ], EnrichmentBrowser [ 59 ], Piano [ 60 ] and decoupleR [ 61 ] as well as the ML-based approach, CGPS [ 62 ] and the CPA web application [ 63 ]. Details on each of these ensemble techniques are provided in Supplementary Text 8 (available online at https://academic.oup.com/bib ).…”
Section: Comparative Studies On Enrichment Methodsmentioning
confidence: 99%